Philosophy from an empirical standpoint : essays on Carl Stumpf - Fisette, Denis, 1954-; Martinelli, Riccardo, 1964- (Studien zur Österreichischen Philosophie, 2015)
The purpose of this book is to highlight Carl Stumpf's contributions to philosophy and to assess some of the aspects of his work. This book is divided into four sections, and also includes a general introduction on Stumpf's philosophy. The first section examines the historical sources of his philosophy, the second examines some of the central themes of his work and the third examines his relationship to other philosophers. The fourth section consists of notes taken by Husserl during Stumpf's lectures on metaphysics in Halle, Stumpf's introduction to the edition of his correspondence with Brentano, which he prepared in 1929, and some important letters pertaining to this correspondence. This book also provides a comprehensive bibliography of the works of Stumpf.